Do plasminogen activators play a role in lichen sclerosus? - Farrell, A; Dean, D; Charnock, F; Wojnarowska, F (2000)
The histological changes of lichen sclerosus suggest that significant remodelling of the extracellular matrix is occurring. As the proteases of the plasminogen activator system have been implicated in tissue remodelling, cell migration and tumour invasion, we performed an immunohistochemical study to look for evidence of alteration in the expression of plasminogen/plasmin, urokinase-type plasminogen activator, tissue-type plasminogen activator and alpha2-antiplasmin in biopsies of clinically typical vulval lichen sclerosus obtained from 11 untreated adult women. Normal vulva obtained from gynaecological procedures and samples of the patients' uninvolved thigh tissue were used as controls. No significant difference was seen in the staining pattern between the lichen sclerosus tissue and control tissue. However, although we found no immunohistochemical evidence that the plasminogen activator system is involved in the pathogenesis of vulval lichen sclerosus, it may be that other proteases are involved.